PENINGKATAN DAYA SAING PERANGKAI PAPAN BUNGA DI KECAMATAN SIANTAR UTARA MELALUI ANALISIS DATA PREFERENSI KONSUMEN DAN PELATIHAN PEMASARAN DIGITAL - Rektor Sianturi; Jaya Tata Hardinata; Susy Alestriani Sibagariang; Yuliana Nainggolan; Dian Lestari Hutapea; Perdamaian Pernando Sitanggang; Arda Pakpahan (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to improve the competitiveness of flower board businesses in North Siantar District through consumer preference analysis and the application of digital marketing. Consumer preference data is analyzed to identify the product characteristics that most influence purchasing decisions, which are then used as the basis for developing marketing strategies and product variations. A digital marketing training program is provided to partners to improve their promotional capabilities through digital media and expand their market reach. The results of the implementation show an increase in the number of orders and partner income of 40%–50% per week. In addition, the development of three product packages, namely standard, premium, and deluxe packages, as well as the application of a deluxe package promo with a free standard package, proved to be effective in increasing consumer interest. These results show that the integration of consumer preference analysis and digital marketing can strengthen the competitiveness of flower board businesses in a sustainable manner.